Analysis and development of the spatial and developmental potential of industries in Diyala Governorate for the period (2018- 2030) - Manshid, Ahlam Nuri (Journal of natural sciences, life and applied sciences, 2018)
The study of geographical location is based on the studies that depend on the scientific method and technique، as well as the effect of development and environmental variables and how to characterize them according to efficiency and industrial utilization. The spatial analysis of the pattern of population distribution and its effect on the spatial profiling of industries in 2018 in the cities and centers of the districts of Diyala governorate is presented to give a picture of the relative size of the population، the number of workers and the area of ​​the districts. The number of workers was 1485407، And the industrial density in the districts (Baquba، Muqdadiya، Khalis، Khanaqin، Baldrouz، Kafri) was recorded as follows: 29،35، 14،01، 25،67، 17،04،11،96، The study also examined the nature of indicators of the spatial reality of the structure of the main industries and the extraction of simple correlation coefficients (Pearson) through the use of statistical program sspsV17، the most important of which is the government planning policy (0.94%) followed by marketing plan (0.90%)، and then know the level of settlement rates، as well as the efficiency and utilization of the patterns of basic and alternative industries in the provinces of Diyala in 2018، To be concentrated in the districts of industries (1.1، 1.2، 1.0، 0.3، 1.4 and 0.6) respectively.. Diyala Governorate for the period 2018- 2030، depending on the economic statistics program EVIEWS 10.1 to build realistic development model.
Keywords: profiling; place; industry